(untitled) (European Journal of Health Research, 2019)
The overlap between autism spectrum disorders (ASD) and eating disorders (ED) has been studied for years, finding similarities in certain cognitive characteristics. The aim of this study is to analyze the available literature about the relationship between autism spectrums symptoms with different pathologies which are include in eating disorders. Information was collected from different databases (Pubmed, Cochrane, Tripdatabase, UpToDate) between 2013 and 2018. Descriptors as "eating disorders", "autism", "treatment", "psychotherapy", "anorexia nervosa”, are used. "Bulimia nervosa", "food avoidant / restriction intake disorder", "binge eating disorder", "obesity" and "adolescence" and the same ones in Spanish are used. The published studies, referred throughout the text, mainly refer to anorexia nervosa (AN) with less research in others eating disorders such as obesity, bulimia, and binge eating disorder. However, despite of the fact that the relationship with the AN is especially mentioned, there are cognitive characteristics that are shared between the ED and the ASD that must be taken into account due to their implications, not only in treatment, also in the prognosis.